Disease Control Priorities, Third Edition : Volume 1. Essential Surgery - Debas, Haile T. (Washington, DC: World Bank, 2015)
Essential Surgery is the first volume in the Disease Control Priorities, third edition (DCP3) series. DCP3 endeavors to inform program design and resource allocation at the global and country levels by providing a comprehensive review of the effectiveness, cost, and cost-effectiveness of priority health interventions. The volume presents data on the surgical burden of disease, disability, congenital anomalies, and trauma, along with health impact and economic analyses of procedures, platforms, and packages to improve care in settings with severe budget limitations.